Vermicompost, Mulching and Irrigation Level on Growth, Yield and TSS of Tomato (Solanum lycopersicum L.) - SINGH, B. K.; PATHAK, K. A.; RAMAKRISHNA, Y.; VERMA, V. K.; DEKA, B. C. (Indian Journal of Hill Farming, 2014)
A field experiment was conducted for two years to investigate the effect of vermicompost, organic mulching and irrigation level on growth, yield and quality attributes of tomato (Solanum lycopersicum L.) with an ultimate aim of optimizing water and nutrient requirement of tomato in mild-tropical climate during dry season. The vermicompost together with organic mulching increased plant height (106.5 cm), leaf area (40.6 cm2), leaf weight (1301 mg/ leaf), fruit weight (92.9 g), fruit yield (4.013 kg/ plant), fruit density (0.972 g/ cc), post-harvest shelf-life (15.0 days) and TSS (5.2Âº Brix) of tomato significantly. Application of vermicompost alone too increased the shelf-life of fruits by 25-106 % and TSS beyond 4.5 %, both of which are traits highly desirable for production of summer tomato and the related processing industry. The application of vermicompost @ 5 tonnes/ ha, 5 cm thick mulching with dried crop residues, two-thirds dose of NPK fertilizer (80:40:40 kg/ ha) and 30 % irrigation is optimum for obtaining better quality and productivity of field grown tomatoes during dry period of mild-tropical climate.